1984
DOI: 10.1093/ptj/64.7.1067
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Timed Balance Test Scores with Aging

Abstract: This study investigated whether 184 volunteers from 20 to 79 years of age could perform eight timed balance tests and examined the relationship between test performance and age. All subjects were able to balance with their feet together and eyes closed for 30 seconds. The ability to balance on the right and left legs did not differ significantly. Subjects over 60 years of age were unable to balance on one leg, particularly when their eyes were closed, for as long a period as younger subjects. The Pearson produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
270
7
14

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(306 citation statements)
references
References 9 publications
15
270
7
14
Order By: Relevance
“…Bohannon et al (1984) and Bohannon (1987), measuring the ability to balance with the eyes open or closed and the feet together in normal subjects 20 to 79 years old and in hemiplegic patients, reported that dysfunction of balance correlated strongly with age and the ability to walk, i.e., the balance decreased with age and that as the balance improved, so did gait performance. In stroke, unilateral hemispheric lesions could bring about dysregulation of posture, balance and locomotion, thus producing instability in standing and gait abnormality and peripherally weakness of the affected lower limb muscles as well as mediolateral instability of the ankle joint would increase body sway and hinder walking performance (Perry 1969;Nakamura et al 1985;Lehman et al 1987 ;Nakamura and Hosokawa 1988).…”
mentioning
confidence: 99%
“…Bohannon et al (1984) and Bohannon (1987), measuring the ability to balance with the eyes open or closed and the feet together in normal subjects 20 to 79 years old and in hemiplegic patients, reported that dysfunction of balance correlated strongly with age and the ability to walk, i.e., the balance decreased with age and that as the balance improved, so did gait performance. In stroke, unilateral hemispheric lesions could bring about dysregulation of posture, balance and locomotion, thus producing instability in standing and gait abnormality and peripherally weakness of the affected lower limb muscles as well as mediolateral instability of the ankle joint would increase body sway and hinder walking performance (Perry 1969;Nakamura et al 1985;Lehman et al 1987 ;Nakamura and Hosokawa 1988).…”
mentioning
confidence: 99%
“…Dada la conformación etaria del grupo de AM, se observa una disminución de rendimiento en la prueba TUG 15-18 y en la EUP 16,[19][20][21] , las cuales fueron menos acentuadas entre los quinquenios tres y cuatro (Tabla 2). Esto se podría explicar dado que estos resultados ocurrieron entre los dos quinquenios del decenio 70-79, en cuyo período también se ubica la esperanza de vida de la población chilena 22 , donde por razones de morbimortalidad, se establecerían condicionantes figura 1.…”
Section: Discussionunclassified
“…This test can be administered with eyes open and eyes closed. 30,31 Individuals with MS have significantly less ability to maintain balance in SLS compared with those without MS. 32 …”
Section: Single-leg Stance (Sls) Testmentioning
confidence: 99%